Technologies supporting independent moving inside buildings for people with visual impairment - Pilski, Marek (Studia Informatica. System and information technology, 2021)
Sustainable Development Goals (SDGs) include disability and persons with disabilities for example partially sighted or blind. Disability is referenced in multiple parts of the SDGs, specifically in the parts related to education, growth and employment, inequality, accessibility of human settlements and buildings. The paper presents selected technologies that support independent movement blind people inside huge buildings. The paper will refer to two SDGs: No 9 and No 11. There needs to be a future in which cities provide opportunities for all with access to basic services, housing, friendly public buildings, transportation and more, even to people with eye disabilities. This paper presents selected systems for finding objects or places, recognizing objects inside rooms and navigation inside buildings based on nonradio and wireless technologies. The following technologies and solutions were presented and compared: physical items, smartphone cameras, laser rangefinders, pedestrian dead-reckoning, intelligent lighting, Wi-Fi, BLE beacons, magnetic fields and barometric pressure sensors.